The impact of platform economy on enterprise value mediated by technological innovation - Pan, Xiongfeng; Wang, Yuqing; Zhang, Chengming; Shen, Zhiyang; Song, Malin (Journal of business research, 2023)
•Development of platform economy helps to enhance enterprises value.•The positive impact was mediated by the technological innovation.•The value of state-owned enterprises is more affected by the platform economy. Platform economy, a new economic form using an internet platform as the primary carrier to promote digital economy, could enhance the enterprise value. The existing researches mainly focus on the platform economy's micro-level effect, such as the performance of the industries. This paper empirically examines the platform economy's micro-level effect, i.e., on enterprise value as mediated by technological innovation, based on data from the listed enterprise from 2015 to 2020. The modeling results show that platform economy improves enterprise value, as supported by the positive value of the regression coefficient. The positive impact was mediated by the technological innovation ability of the enterprises, with a mediating effect of 27.30%. The heterogeneity test results show that platform economy positively impacts the enterprise value of state-owned and non-state-owned enterprises, where the impact is more significant in the former. The government should provide policy and financial assistance to non-state enterprises.